A High‐Efficiency All‐Fiber Laser Operated in High‐Order Mode using Ring‐Core Yb‐Doped Fiber. Issue 10 (20th August 2019) - Li, Hongxun; Zhang, Yimin; Dong, Zhipeng; Lv, Jialiang; Gu, Chun; Yao, Peijun; Xu, Lixin; Zhang, Rui; Su, Jingqin; Chen, Wei; Zhu, Yonggang; Zhan, Qiwen
Abstract: An all‐fiber laser generating a cylindrical vector beam is proposed and demonstrated using a home‐made ring‐core Yb‐doped fiber (RC‐YDF). In the RC‐YDF, not only annular doping but also ring‐type beam pump is realized. This is believed to be the first report describing the realization of annular doping and ring‐type beam pump in active fiber simultaneously, which can enhance the efficiency for high‐order mode oscillation. This laser operates in the high‐order mode stably with a slope efficiency of as high as 55.7%. Cylindrical vector modes can be obtained easily through adjusting the polarization controller. This work may have great potential for providing high‐efficiency and high‐power cylindrical vector beam and vortex beam sources. Abstract : A cylindrical vector beam is generated efficiently using a home‐made ring‐core Yb‐doped fiber (RC‐YDF). Due to the high spatial overlap of the high‐order mode with the annular Yb‐doped region and the ring‐type pump beam in the RC‐YDF, the laser operates in the high‐order LP11 mode stably with a slope efficiency of as high as 55.7%, which can reach 69.6% theoretically.